Traditional vs. Scientific Eri Silkworm Rearing: A Study in Bhubaneswar Zone - Subhrata Jena; Hasansab A. Nadaf; Vishal Mittal; N. B. Chowdary; T. Selvakumar; P. C. Padhy (Archives of Current Research International, 2024)
Sericulture holds significant importance in the tribal economy of India, with the country being the sole producer of various natural silks including mulberry, tasar, muga, oak tasar and eri silk. Eri silkworm rearing is particularly prevalent in the Bhubaneswar zone of Odisha, encompassing districts such as Khurdha, Jagatsinghpur, Nayagarh, Cuttack and Kendrapada. This study focuses on the traditional eri culture methods in the region, highlighting indigenous rearing techniques, food plant selection, larvae management etc. Observations revealed that traditional practices were consistent across the Bhubaneswar region, emphasizing the need for adopting scientific methods. Implementing tray/platform rearing, precise feeding techniques, strategic food plant selection during different larval stages, well-designed rearing rooms and advanced spinning methods can optimize space usage, ensure disease-free larvae, promote uniform cocoon production, increase the effective rate of rearing and silk production. The disparities in shell percentage between cocoons at the farmer level and the farm level in the Bhubaneswar zone are indicative of varying practices and care in sericulture. Farmer-level cocoons exhibit a lower shell ratio ranging from 9.17% to 9.82%, implying inadequate care and nutrition provided to growing silkworms. This discrepancy suggests that these farmers might face challenges in maintaining suitable conditions such as proper temperature, humidity and nutrition, leading to inferior cocoon quality. Conversely, at the farm level, the shell ratio ranges from 10.14% to 10.71%, indicating that farmers in this category are comparatively more adept at silk rearing practices. They provide better nutrition, suitable temperature, humidity and other necessary facilities, resulting in higher-quality cocoons. The superior environment and care provided at the farm level are reflected in the Effective Rate of Rearing (ERR%) consistently above 40%, reaching a maximum of 50.85%. This signifies that farm-level cocoons have better attributes such as cocoon weight, shell thickness and filament size compared to those reared by individual farmers, where ERR% ranged from 31% to 42%. The integration of modern techniques not only enhances production potential but also creates employment opportunities for rural youth. This approach fosters better income generation, surpassing the limitations of traditional methods and paving the way for a thriving sericulture industry.